Impact of the COVID-19 pandemic on epidemiological and clinical characteristics of inpatients with burns in a Northwest China burn centre: a retrospective study - Jiaqi Liu; Jian Feng; Yuheng Zhang; Yiwei Cui; Shuao Xiao; Yige Han; Yongqian Bian; Xueyong Li (BMJ Open)
Objective This study aimed to assess the impact of the COVID-19 pandemic on the characteristics and outcomes of patients with burns in a burn centre situated in Northwest China.Design A retrospective descriptive study.Setting This study was conducted in Tangdu Hospital, a major regional burn centre in Xi'an, Shaanxi Province of China.Participants A total of 1413 patients with burns were included in the study, with the admission period spanning from 2017 to 2019 (before the pandemic) and 2020 to 2022 (during the pandemic).Results Burn hospitalisations decreased during the pandemic for both children (9.80%) and adults (24.68%). The pandemic was associated with a decrease in work-related burns and a corresponding increase in the risk of domestic burns (both p<0.001). The proportions of burns due to scald and flame increased, while electrical injury cases and proportions decreased significantly (both p=0.001). The estimated range of % total body surface area (TBSA) for children increased from 8% (IQR: 5–12%) to 10% (IQR: 8–15%) in children (p<0.001) and from 8% (IQR: 4–18%) to 11% (IQR: 6–25%) in adults (p<0.001). In children, the number of burn cases transferred from other hospitals decreased (p=0.011). Among adults, the number of female patients with burns rose (p=0.013), and the number of patients with inhalation injury also rose (p=0.009).Conclusion During the COVID-19 pandemic, the number of inpatients with burns declined. Domestic burns became more common, and scald and flame burns as well as the average burn area (% TBSA) increased. These findings might highlight the significance of implementing specific public health strategies and safety measures to improve family safety both during and after the pandemic.